Validity and reliability of clothing fashion design (CFaDC) competency instrument - Kamis, Arasinah; Bakar, Ab. Rahim; Hamzah, Ramlah; Asimiran, Soaib (IDOSI Publications, 2014)
This research intends to determine the validity and reliability of Clothing Fashion Design (CFaDC) Skills instrument among instructors (ITR) in Skills Training Institutes (STI). This instrument was administered on 330 instructors in STI that teaches in the field of fashion and clothing. Rasch Measurement Model and Confirmatory factor analysis (CFA) were used to evaluate the construct validity of this instrument. The CFaDC have reached the Cronbach alpha > 0.7 for the reliability of six sub constructs of skills competency. This instrument also obtained consistent and good internal validity which were convergent and discriminant validity. The goodness-of-fit measure of CFI, IFI, TLI > 0.90 and RMSEA < 0.08 further proved the construct validity. In summary, the research findings showed that the CFaDC instrument achieved sound psychometric properties and can be used to measure the competency level of instructors in STI.